2023
DOI: 10.3390/ijms24044204
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine-Mediated Recruitment of GABAergic Neurons to a Dopaminergic Phenotype Attenuates Motor Deficits in an Alpha-Synuclein Parkinson’s Model

Abstract: Previous work revealed an inverse correlation between tobacco smoking and Parkinson’s disease (PD) that is associated with nicotine-induced neuroprotection of dopaminergic (DA) neurons against nigrostriatal damage in PD primates and rodent models. Nicotine, a neuroactive component of tobacco, can directly alter the activity of midbrain DA neurons and induce non-DA neurons in the substantia nigra (SN) to acquire a DA phenotype. Here, we investigated the recruitment mechanism of nigrostriatal GABAergic neurons t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 70 publications
0
4
0
1
Order By: Relevance
“…In addition, TH, a rate-limiting enzyme in dopamine synthesis, typically shows decreased expression in PD [ 38 ], serving as a marker for the loss of dopaminergic neurons. In parallel, we observed that elevated levels of α-synuclein, a protein implicated in PD pathogenesis due to its tendency to form toxic aggregates [ 39 ], were significantly reduced following SAL treatment. This dual modulation of TH and α-synuclein by SAL highlights its potential as a targeted therapeutic strategy against the core pathological features of PD [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TH, a rate-limiting enzyme in dopamine synthesis, typically shows decreased expression in PD [ 38 ], serving as a marker for the loss of dopaminergic neurons. In parallel, we observed that elevated levels of α-synuclein, a protein implicated in PD pathogenesis due to its tendency to form toxic aggregates [ 39 ], were significantly reduced following SAL treatment. This dual modulation of TH and α-synuclein by SAL highlights its potential as a targeted therapeutic strategy against the core pathological features of PD [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, using D-line α-Syn transgenic mice, and a humanized neuronal model of synucleinopathies, it was revealed that nicotine via activation of α4β2 nicotinic receptors attenuates α-Syn-provoked neuropathology [194]. In a similar in-vivo study, it was shown that nicotine attenuates motor deficits in an α-Syn PD model [195]. Thus, manipulating both α4β2 and α7nAChRs may effectively mitigate synucleinopathies [178,194,196].…”
Section: Nicotine For Pdmentioning
confidence: 96%
“…Activity induced-changes in neurotransmitter identity can substantially impact the ability of the individual to deal with the environment, by promoting either advantageous or disadvantageous changes in behavior. Beneficial effects have been linked to changes in the transmitter identity of midbrain neurons and could pave the way for novel treatment opportunities in motor and neurodegenerative disorders ( Table 1 ; Steinkellner et al, 2018 , 2022 ; Li and Spitzer, 2020 ; Lai et al, 2023 ). In contrast, changes in the neurotransmitter phenotype of hypothalamic neurons cause stress-induced behaviors in response to seasonal changes in photoperiod length ( Dulcis et al, 2013 ; Porcu et al, 2022 ).…”
Section: Neurotransmitter Switching: Electrical Activity Regulates Ne...mentioning
confidence: 99%
“…These promote the development and use of quantitative resources to understand brain circuits from cellular to behavioral scales and across multiple species. Some outcomes include progress in the neuromodulation of the spinal cord for motor recovery after stroke (Powell et al, 2023), DBS personalization in the treatment of resistant depression, and the identification of neuronal signatures predicting pain in the brain of patients with chronic pain, by the use of intracranial electrodes (Shirvalkar et al, 2023). This is a continuously growing field, which demands the integration of multiple disciplines, and has led to the creation of consortiums for data management to understand the nervous system.…”
Section: Neurogliopathologyunclassified